Effects of short-term very low-calorie diet on metabolic profile in patients with metabolic syndrome - Zhou, Yi; Li, Shu-nan; Hu, Tianchi; Hu, Shang-qing; Li, Na-fen; Fan, Yan-jing; Yu, Jing-wen; Yuan, Yuan; Chen, Ying-xin; Sun, Min-xing; Chen, Hong-hua; Li, Bo; et al. (Frontiers in Endocrinology, 2025)
BackgroundAccumulating evidence indicates that dietary modifications confer beneficial effects on metabolic syndrome (MetS). In clinical practice, short-term very low-calorie diets (VLCD) have been established as an effective intervention for improving MetS, even in the absence of exercise. However, the impact of a short-term VLCD on the serum metabolic profile of patients with MetS remains to be elucidated.Methods18 adult patients meeting the diagnostic criteria for MetS were enrolled and placed on a 9-day VLCD regimen. Anthropometric parameters, blood pressure, and lipid metabolism indices were measured before and after the intervention. Serum metabolic profiles were subsequently acquired using 1H-NMR spectroscopy.ResultsFollowing the short-term VLCD intervention, patients with MetS exhibited significant reductions in body weight, waist circumference, and BMI (P < 0.05). Blood pressure was also significantly lowered (P < 0.05). Furthermore, the intervention regulated both glucose and lipid metabolism. Serum metabolomic analysis identified 20 characterized metabolites, all of which showed significantly decreased levels post-treatment (P < 0.05). Pathway analysis indicated that the short-term VLCD modulated key metabolic pathways involved in energy and lipid metabolism, insulin sensitivity, anti-inflammatory and antioxidant responses, cellular signaling, and neurohormonal regulation.ConclusionsOur study demonstrates that a short-term VLCD is an effective and safe intervention for improving anthropometric parameters, blood pressure, and lipid metabolism in patients with MetS. The observed therapeutic effects appear to be mediated through a remodeling of the serum metabolic profile and a concomitant modulation of key metabolic pathways. These findings provide a scientific rationale for the clinical application of short-term VLCD in MetS management.